Critical Evaluation Analysis of the Role of Government in the School of German Ordoliberalism in Persian Language Sources - Saeed Seyed Hosseinzadeh Yazdi; Mohammad javad Sharifzadeh; Adel Paighami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The study of the role of government in the school of German Ordoliberalism in order to be considered as an alternative to the neoliberal capitalist system after the global crisis of 2008 and influencing the development model of West Germany after World War II and its effects on the model of EU governance and some other countries are important. The purpose of this article is to review, evaluate and critique the analysis" of works produced and translated into Persian in this field. some suggestions were made as follows: citing sources and first-hand thinkers of this school, distinguishing between similar concepts, correcting in-text references and equations Making specialized reforms, using valid analysis methods, paying attention to the foundations of ontology, anthropology, arithmetic, and ethics and its effect on the role of the government in this school and its critique from an Islamic perspective, and finally paying attention to different dimensions of the role of the state in this school, including the role of the economic constitution, social policy, and finally the presentation of an analytical model of concepts related to the role of the state and the relations and interactions between them.